2002
DOI: 10.1088/0031-9155/47/16/314
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric considerations for validation of a sequential IMRT process with a commercial treatment planning system

Abstract: Commercial multileaf collimator (MLC) systems can employ leaves with rounded ends. Treatment planning beam modelling should consider the effects of transmission through rounded leaf ends to provide accurate dosimetry for IMRT treatments delivered with segmented MLC. We determined that an MLC leaf gap reduction of 1.4 mm is required to obtain an agreement between calculated and measured profile 50% dose points. A head and neck dosimetry phantom, supplied by the Radiological Physics Center (RPC), was planned and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 4 publications
0
54
1
1
Order By: Relevance
“…4 However, with the advent of these new techniques come new problems for performing direct, accurate dosimetry measurements of small radiation fields. Discrepancies have been reported between doses predicted by treatment planning systems and those measured in patients or phantoms, [5][6][7][8] and sophisticated Monte Carlo codes have been used to calculate the dose properties of small fields in lieu of direct measurements, which may be too difficult to perform with typical detectors. [8][9][10][11] Moreover, the rapid advance of small-field radiotherapy technology has precipitated a decrease in the relevance of well-established standards of practice with respect to reference dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…4 However, with the advent of these new techniques come new problems for performing direct, accurate dosimetry measurements of small radiation fields. Discrepancies have been reported between doses predicted by treatment planning systems and those measured in patients or phantoms, [5][6][7][8] and sophisticated Monte Carlo codes have been used to calculate the dose properties of small fields in lieu of direct measurements, which may be too difficult to perform with typical detectors. [8][9][10][11] Moreover, the rapid advance of small-field radiotherapy technology has precipitated a decrease in the relevance of well-established standards of practice with respect to reference dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…-Inadequate modeling of the penumbra at MLC leaf ends [17] -Incorrect application of QA calculations or measurements The RPC recently evaluated the deviation rates of several trials that required credentialing for some or all participants [5,18,19]. The results, shown in Table 2, indicated that trials requiring credentialing experienced low deviation rates.…”
Section: Results Of Credentialingmentioning
confidence: 99%
“…[36][37][38][39][40] Therefore, it is rec- Another type of small-field dosimeter that has been used in IMRT is the thermoluminescence dosimeter ͑TLD͒. [55][56][57][58][59][60][61][62][63][64][65][66][67][68] TLD dosimetry has been used since the 1970s to quantify megavoltage x-ray dosimetry. [69][70][71][72][73] A TLD is an integrating dosimeter, which is usually small in size, often in the form of a cubical or cylindrical chip, and has a nearly tissueequivalent atomic composition ͑Z = 8.1͒ and a typical physical density of 2.6 g cm −3 .…”
Section: Iia1c Ionization Chamber Stabilitymentioning
confidence: 99%
“…In spite of the added difficulty, anthropomorphic phantoms have been effectively used for limited measurements to evaluate the process of patient treatment planning and delivery and to identify treatment planning or dose delivery problems that are not evident in simple homogeneous geometric phantoms. 59,[155][156][157] The phantom setup typically parallels a human simulation and irradiation. For example, a CT simulation of the phantom should be conducted using radiopaque and visible fiducial markers, and when possible, the phantom position should be independently verified, for example using an electronic portal imaging device ͑EPID͒ or film at the treatment unit before delivery.…”
Section: Iiia3 Anthropomorphic Phantomsmentioning
confidence: 99%